Light-induced excited spin state trapping in iron(iii) complexes. Issue 2 (26th November 2020) - Nakaya, Manabu; Ohtani, Ryo; Lindoy, Leonard F.; Hayami, Shinya
Abstract : This review discusses the correlation of the local and whole molecular structure of iron(iii ) complexes with the magnetic properties including the light-induced excited spin-state trapping (LIESST) effect. Abstract : Spin crossover in iron(ii ) and iron(iii ) complexes continues to receive much attention for the construction of molecular devices due to the presence of functionalities arising from their spin state switching behavior. Notably, some such compounds are associated with a light-induced excited spin-state trapping (LIESST) effect, which is responsible for the optical switching of their spin states. However, as opposed to iron(ii ) complexes, reports of iron(iii ) complexes that exhibit a LIESST effect are somewhat limited. This review presents an overview of the reported examples of SCO iron(iii ) systems that display LIESST effects.